KREATIVITAS DAN HASIL BELAJAR SISWA: DAMPAK STRATEGI PEMBELAJARAN MASTERY LEARNING DALAM PENGAJARAN BAHASA INDONESIA - Farida Ariani; Joni Indra Wandi; Nora Afnita (COLLASE (Creative of Learning Students Elementary Education), 2021)
Indonesian language teaching is a very important subject because in daily life students will always be related to their mother tongue. In order to understand the concept of language especially writing narrative essays well by students, the mastery learning strategies are needed. The purpose of this study was to explain the extent to which students' creativity and learning outcomes can be improved through this strategy when compared to conventional strategies. The research method was quantitative research with a quasi-experimental design. The research instrument used observation sheets and test writing narrative essays. The results showed that the mastery learning strategy was more effective compared to the conventional one in increasing students’ creativity and learning outcomes in the classroom.